The Utility of Simulation in the Management of Patients With Congenital Heart Disease: Past, Present, and Future. (March 2018) - Subat, Ali; Goldberg, Andrew; Demaria, Samuel; Katz, Daniel
Significant advancements have been made in the diagnosis and management of congenital heart disease (CHD). As a result, a higher percentage of these patients are surviving to adulthood. Despite this improvement in management, these patients remain at higher risk of morbidity and mortality, particularly in the perioperative setting. One new area of interest in these patients is the implementation of simulation-based medical education. Simulation has demonstrated various benefits across high-acuity scenarios encountered in the hospital. In CHD, simulation has been used in the training of pediatrics residents, assessment of intraoperative complications, echocardiography, and anatomic modeling with 3-dimensional printing. Here, we describe the current state of simulation in CHD, its role in training care providers for the management of this population, and future directions of CHD simulation.